A Biomechanical Study of a Novel Asymmetric 6-Strand Flexor Tendon Repair Using Porcine Tendons. (January 2018) - Wong, Yoke Rung; Tay, Shian Chao
Background: This study evaluated the biomechanical performance of a novel asymmetric 6-strand flexor tendon repair technique without locking loops.Methods: Twenty porcine flexor tendons were equally repaired by using the asymmetric technique and compared with the modified Lim-Tsai repair technique. The ultimate tensile strength, load to 1-mm gap force, stiffness, and mechanism of failure were measured.Results: The asymmetric repair technique had significantly higher tensile strength (63.3 ± 3.7 N) than the modified Lim-Tsai repairs (46.7 ± 8.3 N).Conclusions: A novel flexor tendon repair technique with improved biomechanical performance may be available for use in flexor tendon repairs.